Koneksi Politik, Kepemilikan Pemerintah dan Pengungkapan Sustainability Reporting - Sutawan, Made Danartha; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi; Vol 32 No 8 (2022), 2022)
Sustainability reporting is a report that contains information outside the company's financial performance. In recent years, there are much increase in the disclosure of sustainability reporting in Indonesia. The purpose of this study is to explain how political connections and government ownership affect the disclosure of sustainability reports. This research was conducted at companies from Indonesia that were ranked on ASRRAT in 2018-2020. Determination of the sample using a purposive sampling method with two criteria, such as companies that publish annual reports and sustainability reports from 2017-2019. The data in this study were analyzed using multiple linear regression analysis techniques. The results of this study indicate that political connections have a positive effect on the disclosure of the sustainability report, but government ownership does not affect the disclosure of the sustainability report. The results of this study also prove there is evidence from the theory of legitimacy, that is the company has a social contract, namely a sustainability report with its environment. Keywords: Sustainability Report; Political Connection; Government Ownership